Does trade imply convergence? Analyzing the effect of NAFTA & distance on the local convergence in Mexico - Alberto Díaz Dapena; Esteban Fernandez Vazquez; Rafael Gardu\~no; Fernando Rubiera Morollón (European Regional Science Association (ERSA), 2015)
Regional Economics and Economic Growth focus on the question of trade leads to a greater concentration of economic activity. Yet little empirical work has assessed the regional convergence impacts of trade. Therefore this paper studies the regional convergence from trade in Mexico after NAFTA. Unlike previous papers, working with municipal-level data allows to observe more clearly the convergence patterns across space and to identify the effect of NAFTA, respectively. Result shows that after NAFTA, convergence in regions near the U.S. border grew faster than those further away. However, there is a significant reduction of the beta coefficient after NAFTA indicating a slowdown in the convergence rate. Additional, we find that those municipalities in the south have not been integrated in the world markets, and have, instead, lagged behind their counterparts after NAFTA.
Keywords: R11; R15; 330; Convergence; local level; clusters; international trade; NAFTA and Mexico